1992
DOI: 10.1002/bjs.1800790914
|View full text |Cite
|
Sign up to set email alerts
|

Selection for screening for familial aortic aneurysms

Abstract: The reported familial clustering of abdominal aortic aneurysm (AAA) indicates the possible rewards of family-based screening programmes with respect both to the number of asymptomatic aneurysms detected and to identifying associated genes. Ultrasonographic screening of 28 families (25 brothers and 28 sisters) was carried out together with collecting a history and a blood sample for analysis of the cholesterol level and genetic markers. Among the screened siblings six (11 per cent), all > 60 years old, had an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 16 publications
0
13
0
3
Order By: Relevance
“…1 Case series have reported increased familial risk for AAA and several studies have reported a high prevalence of AAA among siblings of AAA patients. [2][3][4] Case-control studies have shown an approximately four-fold increased risk being affected for firstdegree relatives of AAA patients. 5,6 These studies are mostly based on consecutive patient series from one or few centers, and few population-based reports covering the subject can be found.…”
mentioning
confidence: 99%
“…1 Case series have reported increased familial risk for AAA and several studies have reported a high prevalence of AAA among siblings of AAA patients. [2][3][4] Case-control studies have shown an approximately four-fold increased risk being affected for firstdegree relatives of AAA patients. 5,6 These studies are mostly based on consecutive patient series from one or few centers, and few population-based reports covering the subject can be found.…”
mentioning
confidence: 99%
“…18 Screening brothers of patients with aneurysms renders an incidence of aneurysms of 20% to 29%. 19 Therefore, we expect that ultrasound screening of the 26 families with familial nonsyndromic TAA will find additional affected patients and permit more accurate pedigree analysis.…”
Section: Commentmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Risk factors for development of AAA include age, male sex, smoking, hypertension, and a positive family history, whereas African Caribbean individuals and diabetic patients are at reduced risk. 6,[9][10][11] Most AAAs remain asymptomatic until rupture occurs. The overall mortality rate after rupture is 65% to 85%.…”
mentioning
confidence: 99%